Studi Literatur: Efektivitas Penggunaan Media Pembelajaran Microsoft Powerpoint terhadap Hasil Belajar Matematika Siswa - Siti Hujaemah; Agung Prasetyo Abadi (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2022)
The purpose of this study is to see how effective Microsoft Powerpoint learning media is at improving students' math learning outcomes. The type of research employed was a literature review based on the findings of previous studies. The data collected in this study uses data from various literature that are appropriate to the topic of discussion and refers to several reference materials, including: Google Scholar, Mendeley, and Harzing. In the literature review study results of all the articles used as references, seven research results were selected for further analysis. The conclusions obtained from this literature study are that Microsoft Powerpoint-based learning media has effectiveness in the process of learning and also has a significant effect on mathematical learning outcomes.